The European Voter 2005
DOI: 10.1093/0199273219.003.0008
|View full text |Cite
|
Sign up to set email alerts
|

8 Issue Voting

Abstract: The main research question in this chapter is to what extent and how voters’ perceptions of important issues affect the outcome of the election. The analyses clearly demonstrate that issue voting matters. If a voter thinks that a certain issue is salient, this has a considerable positive effect on the probability that he or she will vote for the party that is regarded as the ‘owner’ of the issue. Despite thelimitations of the measurements and data used, it is argued that issues do matter in modern elections. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 97 publications
2
29
0
1
Order By: Relevance
“…I would argue that the theoretical and empirical evidence is strong enough to allow for a generalization to a larger period of time. Research shows that the salience of social policy has been high but not overwhelmingly in the 1980s and 1990s and accordingly comparable to what has been found for the sample of this study (Rattinger, 1990;Ku¨chler, 1991Ku¨chler, , 1994Roller, 1998;Aardal and Wijnen, 2005). This gives raise for the expectation that social policy performance effects have been comparable to what is found in the context of this study.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…I would argue that the theoretical and empirical evidence is strong enough to allow for a generalization to a larger period of time. Research shows that the salience of social policy has been high but not overwhelmingly in the 1980s and 1990s and accordingly comparable to what has been found for the sample of this study (Rattinger, 1990;Ku¨chler, 1991Ku¨chler, , 1994Roller, 1998;Aardal and Wijnen, 2005). This gives raise for the expectation that social policy performance effects have been comparable to what is found in the context of this study.…”
Section: Resultssupporting
confidence: 88%
“…A look in the literature makes clear that issues taking this form are seen as rather influential as it has been shown that performance effects are usually stronger than position effects and retrospective evaluations have more weight than prospective ones (see, for example, Wattenberg, 1995;Kra¨mer and Rattinger, 1997;Nagler, 1998, 1995;Clarke et al, 2004;Veiga and Veiga, 2004;Aardal and Wijnen, 2005;Listhaug, 2005;Whiteley et al, 2005, but see also MacKuen et al, 1992;MacKuen et al, 1996;Norpoth, 1996). Political psychology literature teaches us further that only highly salient attitudes have an effect on behavior (see, for example, Fazio, 1986Fazio, , 1989Aldrich et al, 1989), therefore we expect the issue of social policy to be influential particularly for people rating the topic highly important.…”
Section: Issue Voting and Electoral Consequences Of Social Policymentioning
confidence: 99%
See 1 more Smart Citation
“…class voting), because they like an individual candidate, to punish elite parties, etc. Some say issue voting is increasing as a motivator of electoral choice, and others doubt that this is the case (Aardal and Van Wijnen, 2005). Either way, a key aspect of issue voting is information: people need to be informed about what positions parties have adopted regarding the issues they care about.…”
mentioning
confidence: 99%
“…For instance, social policy and labour market issues are among the top three most salient issues in European elections, and especially in Scandinavia (Aardal and van Wijnen 2005;Oscarsson and Holmberg 2008: 54). In Denmark, 'welfare' has been the single most salient issue in every election since 1994 (Stubager et al 2013: 26).…”
Section: Introductionmentioning
confidence: 99%